The relationship between change-of-direction performance indicators and inter-limb asymmetries in elite youth female basketball players - Arboix-Alió, J.; Buscà, B.; Peralta-Geis, M.; Montalvo, A.; Fort-Vanmeerhaeghe, A. (Journal of Human Kinetics, 2025)
The purposes of this study were to characterize the magnitude and the direction of inter-limb asymmetries in elite youth female basketball players and to evaluate any associations with indicators of change-of-direction (COD) performance. Eighteen elite youth female basketball players (17.79 ± 0.67 years; 71.10 ± 7.43 kg; 1.82 ± 0.07 m; 23.01 ± 1.69 kg·(m2)-1) participated in a battery of tests, including 70° and 180° COD, single-leg countermovement jump (SLCMJ), and single-leg drop jump (SLDJ) tests. Inter-limb asymmetry indices (ASIs) were calculated, and correlations with COD performance indicators were examined. The results indicated significant differences between dominant and non-dominant limbs in all tasks, with ASI values ranging from 3.02% to 27.8%. Directionality of asymmetry varied across tests. Correlation analysis revealed that greater asymmetry was associated with slower COD performance (p range = -0.67 to 0.57). Moreover, asymmetry in some tasks was related to lower ground reaction forces (GRFs) (p range = -0.60 to -0.42) and higher contact times during COD 180° (p = 0.45). The results of this study support the need to address inter-limb asymmetries in basketball players. Coaches and practitioners should consider targeted interventions to minimize asymmetry and enhance COD skills. A comprehensive battery of fitness assessments is recommended to provide a holistic understanding of inter-limb asymmetries.